Dorsal Versus Ventral Oral Mucosal Graft Urethroplasty - Hosseini, Jalil; Kaviani, Ali; Hosseini, Mokhtar; Mazloomfard, Mohammad Mohsen; Razi, Abdollah (Urology Journal, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Purpose: To evaluate success rate of dorsal versus ventral oral mucosal graft for anterior urethroplasty. Materials and Methods: In a retrospective study, the results of the ventral and dorsal oral mucosal graft (OMG) anterior urethroplasty were assessed in 24 and 29 patients, respectively. Demographic and clinical characteristics of subjects were gathered from the medical records. Results: Patients were followed up for a mean duration of 32 months (range, 25 to 51 months). The success rates of dorsal and ventral anterior OMG urethroplasty were 83.3% and 75.8%, respectively (P = .5). At penile site, dorsal and ventral OMG were done for 9 and 10 patients with stricture lengths of 3.7 ± 1.1 cm and 3.9 ± 1.2 cm, respectively (P = .7). Success rates of dorsal and ventral penile OMG were 88.9% and 70%, respectively (P = .3). At the bulbar site, dorsal and ventral OMG were performed on 15 and 19 patients with stricture lengths of 4.1 ± 1.1cm and 4.2 ± 1.5 cm, respectively (P = .7). The success rates of dorsal and ventral bulbar OMG were 80% and 79%, respectively (P = .94). Conclusion: Oral mucosal graft is a versatile and an effective procedure for management of strictures throughout the anterior urethra, and in experienced hands, the outcomes are similarly favorable whether a dorsal or ventral approach is taken.